Accurate quantum wave packet calculations for the F plus HCl ? Cl plus HF reaction on the ground 12A? potential energy surface - Bulut, Niyazi; Klos, Jacek; Alexander, Millard H. (Amer Inst Physics, 2012)
We present converged exact quantum wave packet calculations of reaction probabilities, integral cross sections, and thermal rate coefficients for the title reaction. Calculations have been carried out on the ground 1(2)A ' global adiabatic potential energy surface of Deskevich et al. [J. Chem. Phys. 124, 224303 (2006)]. Converged wave packet reaction probabilities at selected values of the total angular momentum up to a partial wave of J = 140 with the HCl reagent initially selected in the v = 0, j = 0-16 rovibrational states have been obtained for the collision energy range from threshold up to 0.8 eV. The present calculations confirm an important enhancement of reactivity with rotational excitation of the HCl molecule. First, accurate integral cross sections and rate constants have been calculated and compared with the available experimental data. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.3692328]
Keywords: Deuterium-Isotope Variants; Reaction Probabilities; Hydrogen Abstraction; Scattering; Atoms; Cl+Hf; F+Hcl